FACIAL ANAMNESIS AS A STAGE IN THE PLANNING OF AESTHETIC TREATMENTS (CIPEEX, 2025)
Facial anamnesis is a crucial phase in the planning of aesthetic treatments, as it allows a comprehensive evaluation of the individual characteristics of each patient. This approach aims to gather detailed information about skin conditions and facial features, providing a deeper understanding of dermatological issues and the client's personal preferences. In addition, the anamnesis covers not only the evaluation of the physical aspects, but also the emotional and psychological factors that can impact the aesthetic results. This narrative review aims to examine the relevance of facial anamnesis in the planning of aesthetic treatments, based on scientific articles published in the last five years. To this end, searches were carried out in databases such as PubMed, Scielo, and Google Scholar, using the terms "facial anamnesis," "aesthetic treatment planning," and "facial aesthetics." Studies published between 2018 and 2023 that addressed the importance of facial anamnesis in the aesthetic context were included. The reviewed articles highlight that facial anamnesis is essential to identify the anatomical and functional characteristics of the face, as well as the emotional and psychological aspects that can influence aesthetic results. The personalization of treatments, based on a detailed anamnesis, proved to be effective in reducing complications, improving patient satisfaction, and optimizing results. In addition, the anamnesis facilitates communication between the professional and the patient, ensuring that expectations are realistically aligned. Facial anamnesis has proven to be an indispensable tool in the planning of aesthetic treatments, contributing to the personalization of interventions and, consequently, to better clinical results and greater patient satisfaction. Recent literature reinforces the importance of this practice, suggesting that a detailed anamnesis should be a mandatory step in any aesthetic treatment plan.
Keywords: anamnesis; planning; facial; aesthetics